Enhancement of alcohol drinking in mice depends on alterations in RNA editing of serotonin 2C receptors. (May 2014) - Watanabe, Yoshihisa; Yoshimoto, Kanji; Tatebe, Harutsugu; Kita, Masakazu; Nishikura, Kazuko; Kimura, Minoru; Tanaka, Masaki
Abstract Serotonin 2C receptors (5-HT2CR) are G-protein-coupled receptors with various actions, including involvement in drug addiction. 5-HT2CR undergoes mRNA editing, converting genomically encoded adenosine residues to inosines via adenosine deaminases acting on RNA (ADARs). Here we show that enhanced alcohol drinking behaviour in mice is associated with the degree of 5-HT2CR mRNA editing in the nucleus accumbens and dorsal raphe nuceus, brain regions important for reward and addiction. Following chronic alcohol vapour exposure, voluntary alcohol intake increased in C57BL/6J mice, but remained unchanged in C3H/HeJ and DBA/2J mice. 5-HT2CR mRNA editing frequency in both regions increased significantly in C57BL/6J mice, as did expressions of 5-HT2CR, ADAR1 and ADAR2, but not in other strains. Moreover, mice that exclusively express the unedited isoform (INI) of 5-HT2CR mRNA on a C57BL/6J background did not exhibit increased alcohol intake compared with wild-type mice. Our results indicate that alterations in 5-HT2CR mRNA editing underlie alcohol preference in mice.